Environmental Management Accounting Based on the Tri Hita Karana Concept: Interpretation and Practice at Village Credit Institutions (LPD) in Bali - Komang Adi Kurniawan Saputra; Putu Ayu Sita Laksmi (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to examine how environmental management accounting (EMA) is implemented in Village Credit Institutions (LPDs) in Bali, based on the local wisdom philosophy of Tri Hita Karana. The research approach used was qualitative with an interpretive paradigm, using an intrinsic case study of LPDs across nine regencies/cities in Bali. Data were collected through in-depth interviews with LPD administrators, observation, and document analysis, and then analyzed using thematic analysis techniques. The results indicate that EMA practices in LPDs are not yet formally structured within a monetary accounting system, but have been internalized in values, policies, and decision-making oriented toward harmonious relationships between humans and God (Parahyangan), fellow humans (Pawongan), and the environment (Palemahan). Environmental management is realized through energy savings, waste reduction, environmentally friendly financing, and consideration of ecological aspects in credit granting. The Tri Hita Karana philosophy serves as an ethical and cultural framework that strengthens the legitimacy of sustainable practices, although it is not yet supported by a comprehensive environmental cost measurement system. This research contributes to the development of an EMA concept contextualized with local wisdom and demonstrates that cultural values ​​can be an important foundation for building community-based sustainable banking practices.